Water tank at the entrance of the temple - Temples of India Project Team (Jio Institute, 2024)
In front of the temple lies a water tank, seemingly a later addition as indicated by the presence of chhatris installed at its corners. The water level can be reached by steps. There is a raised platform on one side. The tank is used regularly by the locals for different purposes. However, a clear statement is made on the chhatris emphasizing the importance of maintaining the sanctity and cleanliness of this holy tank.